Desinformação e competências midiáticas: consumo de notícias esportivas pelos jovens paulistas - Carbone, André Ricardo (2022)
Based on concepts and references from media literature, the research aims to investigate how media skills and communication flows of young people from São Paulo state, Brazil, in relation to the media consumption of sports content. Located in the reception field, the qualitative methodological study investigates 12 young people who consider themselves football fans, aged 18 to 21, through semi-structured individual interviews. Half of the young people are studying Journalism and the other half are taking different courses. In the theoretical part, sport is conceptualized, more specifically football, within the culture of consumption and spectacle of the 20th and 21st centuries. It portrays the formation of soccer fans groups through social ties and the media. Finally, it proposes to verify the media skills of access, evaluation and creation, described by numerous media literacy works, and to arrive at reflections that help to understand the media consumption habits of young people born in the digital age in the face of an environment permeated by disinformation. Dynamics of soccer WhatsApp groups and the conscious use of memes, satires and parodies to create sociability were especially analyzed. The main findings of the survey include a strong confidence of young people interviewed in a few traditional media outlets, which not by chance own the rights to broadcast the games; distrust in news of player transfers, with the credibility of media and journalists being seriously affected if negotiations taken for granted do not materialize; distrust of news from vehicles with sensationalist traits in the message, such as photomontages and aggressive headlines; confusion in valuing the impartiality of journalists and commentators; and the voluntary use of memes that spread disinformation, as long as the humor contained in them is shared by other members of the group.